Spanish ‘depalatalization’: the synchronic, diachronic and perception perspectives - Bessett, Ryan M.; Colina, Sonia (Borealis – An International Journal of Hispanic Linguistics, 2017)
Spanish has a restriction on palatal nasals and laterals in the coda causing them to be realized as dental/alveolar coronals. In the onset position, the palatal point of articulation is retained, bello ‘beautiful-masc.’, beldad ‘beauty’; doña ‘Madam’, don ‘Mister’. Alternations such as these led phonologists to propose a rule of depalatalization that turns an underlying palatal nasal/lateral into a coronal (Contreras 1977; Harris 1983). Pensado (1997) and Harris (1999) later tried to debunk this rule, the former on psycholinguistic grounds, and the latter on the basis of the word structure of Spanish (palatals are always followed by –e). More recently, within an optimality-theoretic framework and through loan word evidence, Lloret and Mascaró (2006) argue again in favor of an active process of depalatalization in Modern Spanish. Taking Lloret and Mascaró as its point of departure, this paper expands the discussion on depalatalization to consider diachronic data and the role of the underlying representation and the perception grammar. Historical data supports depalatalization as an active phenomenon in Old and Medieval Spanish; yet the morphophonological alternations cannot be considered active/productive synchronically. Unlike previous serial models of phonology, an OT framework allows for the incorporation of diachronic data into the analysis, thus explaining how the current situation came about and shedding light on synchronic alternations. OT also provides a formalization of the role of the underlying representation in the diachronic change and in synchronic loanword evidence, thus providing support for depalatalization as an active phonotactic restriction.